Is the public healthcare sector a more strenuous working environment than the private sector for a physician?. Issue 1 (February 2013) - Heponiemi, Tarja; Kouvonen, Anne; Sinervo, Timo; Elovainio, Marko
Aims : The present study examined the differences between physicians working in public and private health care in strenuous working environments (presence of occupational hazards, physical violence, and presenteeism) and health behaviours (alcohol consumption, body mass index, and physical activity). In addition, we examined whether gender or age moderated these potential differences. Methods : Cross-sectional survey data were compiled on 1422 female and 948 male randomly selected physicians aged 25–65 years from The Finnish Health Care Professionals Study. Logistic regression and linear regression analyses were used with adjustment for gender, age, specialisation status, working time, managerial position, and on-call duty. Results : Occupational hazards, physical violence, and presenteeism were more commonly reported by physicians working in the public sector than by their counterparts in the private sector. Among physicians aged 50 years or younger, those who worked in the public sector consumed more alcohol than those who worked in the private sector, whereas in those aged 50 or more the reverse was true. In addition, working in the private sector was most strongly associated with lower levels of physical violence in those who were older than 50 years, and with lower levels of presenteeism among those aged 40–50 years. Conclusions : The present study found evidence for the public sector being a more strenuous work environment for physicians than the private sector. Our results suggest that public healthcare organisations should pay more attention to the working conditions of their employees.